Nilai Sosial Dalam Novel 50 Riyal: Sisi Lain Tkw Indonesia Di Arab Saudi Karya Deni Wijaya - Marta Sihombing; Alifiah Nurachmana; Patrisia Cuesdeyeni; Linggua Sanjaya Usop; Yulina Mingvianita (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
The Novel 50 Riyals: The Other Side of Indonesian TKW in Saudi Arabia by Deni Wijaya is a work about the life of Muslim converts who work as TKW. In this novel it is quite interesting to study further scientifically the lives of women working abroad. Therefore, the writer is interested in studying the social values ​​contained in the novel 50 Riyals: The Other Side of Indonesian TKW in Saudi Arabia. The aims of this study were (1) to describe the social value of the main character's affection in the novel 50 Riyals on the Other Side of Indonesian TKW in Saudi Arabia by Deni Wijaya, (2) to describe the social value of the main character's social responsibility in the novel 50 Riyals on the Other Side of Indonesian TKW in Saudi Arabia. Saudi Arabia by Deni Wijaya, and (3) describing the social value of harmony in the life of the main character in the novel 50 Riyals The Other Side of Indonesian TKW in Saudi Arabia by Deni Wijaya. This research uses a descriptive qualitative research type. The data was taken from reading the novel 50 Riyals: The Other Side of Indonesian TKW in Saudi Arabia by Deni Wijaya. Data collection techniques in this study were carried out using the reading and note-taking method, and then identified and analyzed based on the theory of sociology of literature. This study discusses the social values ​​contained in the novel 50 Riyals: Another Side of Indonesian TKW in Saudi Arabia by Deny Wijaya. The researcher found: (1) there were 10 data of social values ​​of affection, 2 data of devotion, 4 data of kinship, 1 data of caring, and 4 data of loyalty. (2) the value of social responsibility as much as 10 data including, a sense of belonging to each other as much as 3 data, empathy as much as 1 data, and discipline as much as 6 data. (3) there are 9 data on social harmony values, 7 data on tolerance, and 2 data on democracy.